Hiperglikemia dan Aterosklerosis Arteri Karotis Interna pada Penderita Pasca Stroke Iskemik - Agus Darmawan; Dodik Tugasworo; Tjokorda Gde Dalem Pemayun (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTHyperglycemia and atherosclerosis of internal carotid artery in post ischemic stroke patientBackground: Atherosclerosis is the primary cause of death in stroke. Marker of atherosclerosis in carotid artery is intima media thickness (IMT) of artery walls. One of trigger atherosclerosis is hyperglycemia. The objective of the study is to investigate the association between hyperglycemia to atherosclerosis of internal carotid artery in post ischemic stroke patient.Methods: A cross sectional design study, patients post ischemic stroke admitted outpatient clinic of neurology department at Dr. Kariadi General Hospital Semarang, start at May 2010 until July 2010. Analysis of atherosclerosis using carotid duplex ultrasound, analysis of hyperglycemia with fasting blood glucose levels, two-hour postprandial glucose levels and also HbA1c levels using bloodvenous in the laboratory of clinical pathology department at Dr. Kariadi General Hospital. Descriptive statistic and logistic regression test were performed to analyze the data.Result: The mean of fasting blood glucose (FBG) levels were 113.93 (SD 42.2) mg/dL, two-hours postprandial glucose (2hPPG) levels were 182.4 (SD 76.5) mg/dL, HbA1c levels were 6.4 (SD 1.5)%. The mean of intima media thickness of internal carotid artery was 1.2 (SD 1.9) mm. No significance difference  between FBG, 2hPPG and A1c (95% CI, p>0.05) to atherosclerosis of internalcarotid artery in post ischemic stroke patient.Conclusion: There are no significant association between hyperglycemia and atherosclerosis of internal carotid artery in post ischemic stroke patient.Keywords: Hyperglycemia, atherosclerosis, post ischemic stroke ABSTRAKLatar belakang: Aterosklerosis merupakan penyebab kematian utama pada stroke. Petanda aterosklerosis di arteri karotis adalah ketebalan tunika intima media intima media thickness (IMT) di arteri tersebut. Salah satu pemicu aterosklerosis adalah hiperglikemia. Tujuan penelitian ini adalah membuktikan pengaruh hiperglikemia terhadap aterosklerosis arteri karotis interna pada penderita pasca stroke iskemik.Metode: Desain penelitian adalah cross sectional, pada penderita pasca stroke iskemik yang kontrol di Poliklinik Saraf RSUP Dr. Kariadi Semarang mulai Mei 2010 sampai Juli 2010. Analisis aterosklerosis menggunakan USG Karotis Duplex, analisis hiperglikemia dengan menganalisis kadar glukosa darah puasa, kadar glukosa darah 2 jam postprandial dan kadar HbA1c menggunakan darah vena di Laboratorium Patologi Klinik RSUP Dr. Kariadi. Data dianalisis dengan statistik deskriptif dan uji regresi logistik.Hasil: Rerata kadar glukosa darah puasa (GDP) 113,9 (SB 42,2) mg/dL, kadar glukosa darah 2 jam postprandial (GD2PP) 182,4 (SB 76,5) mg/dL dan kadar HbA1c 6,4 (SB 1,5)%. Rerata ketebalan tunika intima media arteri karotis interna 1,2 (SB 1,9) mm. Tidak ada hubungan bermakna antara GDP, GD2PP dan HbA1c (95% CI, p>0,05) terhadap aterosklerosis arteri karotis interna pada penderita pasca stroke iskemik.Simpulan: Tidak ada hubungan hiperglikemia dengan aterosklerosis arteri karotis interna pada penderita pasca stroke iskemik.